Racialised prescribing: enacting race/ethnicity in clinical practice guidelines and in accounts of clinical practice. Issue 5 (6th April 2018) - Smart, Andrew; Weiner, Kate
Abstract: This article examines the articulation and enactment of racialised classifications in clinical practice guidelines and in accounts of clinical practice. It contributes to debates about racialisation in medicine and its consequences. The research centred on the case study of prescribing guidelines for hypertension in England and Wales, drawing on documentary sources and semi‐structured expert interviews. We found that conceptual and socio‐political uncertainties existed about how to interpret the designation 'Black patients' and about the practices for identifying patients' race/ethnicity. To 'close' uncertainties, and thus produce the guidelines and treat patients, respondents drew authority from disparate elements of the 'topologies of race'. This has implications for understanding processes of racialisation and for the future use of racialised clinical practice guidelines. We argue that clinical practice guidelines play a 'nodal' role in racialisation by forming an authoritative material connection that creates a path for translating racialised research into racialised healthcare practice, and that they carry with them implicit conceptual and socio‐political uncertainties that are liable to create inconsistencies in healthcare practice.